PENGEMBANGAN MODEL PEMBELAJARAN SOFT SKILL PADA SEKOLAH MENENGAH KEJURUAN - Ansar; Yahya, Muhammad; Mappalotteng, Abdul Muis (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2025)
Unemployment and the competitiveness of human resources are the main challenges for Indonesia, compounded by the demographic bonus of 2030-2040. Industry 4.0 demands adaptive vocational education, focusing on multi-skills, psychomotor skills, and soft skills. Vocational high school graduates often lack mental readiness and soft skills, even though their hard skills are adequate. This research aims to determine the results of developing a soft skills model for Vocational High School teachers, to ascertain whether the developed Vocational High School soft skills model meets the criteria of validity, practicality, and effectiveness, and to understand students' responses to the developed soft skills-based model. This research uses a type of research and development with relevant locations and subjects, through a development procedure that includes needs analysis, model design, material development, program implementation, and model evaluation; the data collected includes both qualitative and quantitative data, using techniques such as interviews, observations, documentation, and questionnaires, which are analyzed using descriptive and inferential data analysis techniques to test the validity, practicality, and effectiveness of the developed product. The research results show that the developed soft skills model meets the criteria of being valid, practical, and effective, and received positive responses from the students. This emphasizes the importance of integrating soft skills into vocational education to enhance graduates' readiness to face the competitive job market in the era of Industry 4.0.